Women’s status, household structure and the utilization of maternal health services in Nepal - Masaki Matsumura; Bhakta B. Gubhaju (Asia-Pacific Population Journal, 2001)
It is well recognized that maternal health services have a critical role to play in the improvement of women’s reproductive health in developing countries (Magadi and others, 2000; Bhatia and Cleland, 1995; Becker and others, 1993; WHO, 1989). It is also well known that the utilization of maternal health services is undoubtedly influenced by the characteristics of the health delivery system such as the availability, quality and cost of the services. However, this does not necessarily mean that where there is a good supply of services, demand is created in and of itself, which will then lead to increased utilization. Thus, there has been considerable debate in the literature recently as to whether the mere provision of health services will lead to increased utilization (Magadi and others, 2000; Obermeyer, 1993; Basu, 1990). It may be true that, even under the same condition of availability, some women are more likely to use maternal health services than others. If so, characteristics of the health delivery system may not be the only explanatory factors for the utilization of maternal health services. Other factors such as the social structure and characteristics of individuals should also be considered in promoting the utilization of maternal health services.